2019
DOI: 10.7717/peerj.7513
|View full text |Cite
|
Sign up to set email alerts
|

Postural control in girls with adolescent idiopathic scoliosis while wearing a Chêneau brace or performing active self-correction: a pilot study

Abstract: Background It is known that adolescent idiopathic scoliosis (AIS) is often accompanied by balance deficits. This reciprocal relationship must be taken into account when prescribing new therapeutic modalities because these may differently affect postural control, interacting with therapy and influencing its results. Objective The purpose was to compare postural control in girls with AIS while wearing the Chêneau brace (BRA) or performing act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…A reasonable explanation of these results assumes that the increased entropy of AIS in the three easier trials is a consequence of the specific experiences of these girls. This group, quite physically active, built their postural strategies in the presence of additional requirements, such as wearing a brace and performing exercises 9 . Adjusting to these additional difficulties caused the need to use more attentional resources, reducing their share in the balance itself.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reasonable explanation of these results assumes that the increased entropy of AIS in the three easier trials is a consequence of the specific experiences of these girls. This group, quite physically active, built their postural strategies in the presence of additional requirements, such as wearing a brace and performing exercises 9 . Adjusting to these additional difficulties caused the need to use more attentional resources, reducing their share in the balance itself.…”
Section: Discussionmentioning
confidence: 99%
“…There is still too little research in the literature that would examine the posture control system in relation to healthy. Our previous work dealt with how girls with AIS do during active self-correction (ASC) and the possibility of scoliosis impact on posture control 9 , 10 . Results seem to account for the desirable changes in postural control that were generated by learned ASC movements.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with moderate curvatures were treated with a Cheneau Brace. This type of brace orthosis has been shown to be effective in treating scoliosis in the mid to long term ( 9 ) and may produce relevant changes in CoP sway ( 10 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Piątek et al [6] reported that performing ASC resulted in a significant backward excursion of the center of pressure (COP) mean position with the concomitant increase in the COP fractality and frequency in the mediolateral (ML) plane. These results seem to account for desirable changes in postural control that were generated by learned ASC movements.…”
Section: Introductionmentioning
confidence: 99%
“…An individual's attention resources and information processing capacity are presumably limited and must be shared among all the tasks being concurrently performed [8]. The everyday routine of AIS patients often requires the simultaneous performance of ASC with other activities of daily living; therefore, a possibility of conflict arises that may adversely affect posture control, as indicated in the recent study by Piątek et al [6]. Accordingly, when two tasks are being performed at the same time, the performance of one or both can be impaired if together, they require attention that exceeds an individual's capacity.…”
Section: Introductionmentioning
confidence: 99%